2005
DOI: 10.1126/science.1108581
|View full text |Cite
|
Sign up to set email alerts
|

H 2 S Induces a Suspended Animation-Like State in Mice

Abstract: Mammals normally maintain their core body temperature (CBT) despite changes in environmental temperature. Exceptions to this norm include suspended animation-like states such as hibernation, torpor, and estivation. These states are all characterized by marked decreases in metabolic rate, followed by a loss of homeothermic control in which the animal's CBT approaches that of the environment. We report that hydrogen sulfide can induce a suspended animation-like state in a nonhibernating species, the house mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
566
2
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 767 publications
(589 citation statements)
references
References 7 publications
16
566
2
5
Order By: Relevance
“…However, it remains to be tested whether exposure to H 2 S increases metabolic rates in P. mexicana in a similar fashion as in some sulfide-adapted invertebrates (Gorodezky and Childress 1994;Schneider 1996), in which case the present study would have overestimated differences in overall energy consumption between sulfidic and nonsulfidic populations. Because H 2 S also blocks cytochrome c oxidase (COX) in the mitochondrial respiratory chain (Cooper and Brown 2008), sulfide exposure can also cause metabolic rate depression (Brauner et al 1995;Blackstone et al 2005;Volpato et al 2008), and this may be particularly relevant for the populations investigated here. Unlike other evolutionarily lineages of sulfide spring Poecilia in southern Mexico that have evolved H 2 S-resistant COXs, sulfide spring populations in the Tacotalpa drainage used in the present study exhibit an H 2 S-susceptible COX similar to that found in ancestral nonsulfidic populations (Pfenninger et al 2014).…”
Section: Metabolic Rate Variation In Sulfidic Environmentsmentioning
confidence: 99%
“…However, it remains to be tested whether exposure to H 2 S increases metabolic rates in P. mexicana in a similar fashion as in some sulfide-adapted invertebrates (Gorodezky and Childress 1994;Schneider 1996), in which case the present study would have overestimated differences in overall energy consumption between sulfidic and nonsulfidic populations. Because H 2 S also blocks cytochrome c oxidase (COX) in the mitochondrial respiratory chain (Cooper and Brown 2008), sulfide exposure can also cause metabolic rate depression (Brauner et al 1995;Blackstone et al 2005;Volpato et al 2008), and this may be particularly relevant for the populations investigated here. Unlike other evolutionarily lineages of sulfide spring Poecilia in southern Mexico that have evolved H 2 S-resistant COXs, sulfide spring populations in the Tacotalpa drainage used in the present study exhibit an H 2 S-susceptible COX similar to that found in ancestral nonsulfidic populations (Pfenninger et al 2014).…”
Section: Metabolic Rate Variation In Sulfidic Environmentsmentioning
confidence: 99%
“…H 2 S can also produce metabolic depression (akin to ''suspended animation'') in small mammals (9,10), and it has been implicated in torpor and hibernation (159,160), anapyrexia (81), and hypoxia-induced radiation resistance (194). H 2 S has also been shown to protect cells from both hypoxiaand hyperoxia-induced redox imbalance and apoptosis (13,83,85,92,101,189,190).…”
Section: General Metabolismmentioning
confidence: 99%
“…H 2 S, or aqueous sulphide, elicits diverse physiological responses, including modulation of blood pressure and reduction of ischemia reperfusion injury [3][4][5] , exertion of anti-inflammatory effects 6 and reduction of metabolic rate 7 . The production of H 2 S is catalysed by the two pyridoxal 5′-phosphate-dependent enzymes, cystathionine β-synthase (CBS) 8 , and cystathionine γ-lyase 9 , and indirectly, via a pyridoxal 5′-phosphateindependent enzyme, 3-mercaptopyruvate sulphurtransferase 10 .…”
mentioning
confidence: 99%